2013
DOI: 10.1111/apa.12404
|View full text |Cite
|
Sign up to set email alerts
|

The effect of person-centred communication on parental stress in a NICU: a randomized clinical trial

Abstract: Our study was unable to demonstrate the effect of person-centred communication using the Guided Family-Centred Care intervention. It may be necessary to replicate the design to address the risk of contamination and add instruments sensitive to human interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 26 publications
(40 reference statements)
4
64
2
2
Order By: Relevance
“…Over the past 25 years several family-centred care programs have been developed and subjected to randomized controlled trials [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. These programs use one or more approaches, such as parent education, provision of psychological support, teaching developmental care, and facilitating better communication, to address a variety of domains including parent-infant interaction, parental knowledge and confidence, and parental stress.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Over the past 25 years several family-centred care programs have been developed and subjected to randomized controlled trials [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. These programs use one or more approaches, such as parent education, provision of psychological support, teaching developmental care, and facilitating better communication, to address a variety of domains including parent-infant interaction, parental knowledge and confidence, and parental stress.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Several studies have identified elevated stress levels among parents at NICUs and the ability of various interventional programs (eg, individual support, education, and communication) that investigated how to reduce parental stress levels 11–21. Studies that explored fathers' needs and experiences during their infant's admission to NICUs1,2,7,9,22 found that fathers require interventions that differ from those provided to mothers 17,19…”
mentioning
confidence: 99%
“…A Danish study of the effect of supportive communication on parental stress in a NICU found no effect on parental stress, but it raised concern about the need to support parents also in periods where the infant's clinical condition was stable and around discharge from the NICU (28). In our study, PreNu parents were closely followed from birth until 52 weeks age, several weeks after discharge.…”
Section: Discussionmentioning
confidence: 99%